The expat gap: Are local-born entrepreneurs in developing countries at a disadvantage when seeking grant funding? - Lall, Saurabh A.; Chen, Li-Wei; Davidson, Abigayle (Public Administration Review)
Donor agencies and foundations use grants to stimulate entrepreneurial growth in developing countries. However, some practitioners have asked whether these grants tend to flow to expatriate entrepreneurs with ties to developed countries (where most grants originate), rather than to local entrepreneurs. This article tackles this question using a data set of 3,434 nascent ventures from 92 developing countries. The authors find that ventures with ties to a developed country are significantly more likely to raise grant financing and in more substantial amounts. Ventures with a founder born in a developed country are the most likely to receive grants, with a weaker effect when considering prior work experience in a developed country. This (3z(Bexpat gap(3y (Bcannot be explained by differences in education level, prior experience, or ties to other developing countries. Donors seeking to support local entrepreneurs in developing countries should consider ways to make their recruitment and selection processes more equitable. - Reproduced.s